Educating Chinese Nurses about Rehabilitation Nursing: Findings from a Single Cohort Quantitative Pilot Project. Issue 4 (12th April 2016) - Mauk, Kristen L.; Li, Pei Ying; Jin, Huilu; Rogers, Julie; Scalzitti, Kristina
Abstract: Purpose: The purpose of this study was to present results of a pilot program to educate nurses in China about rehabilitation nursing. Design: A single cohort, pre‐ and posttest design with an educational intervention. Methods: A 3‐day basic rehabilitation nursing education program was conducted in Shanghai and Hangzhou by a certified rehabilitation nurse specialist from the United States. The effect of the educational intervention was measured using pre‐ and posttests for six topic areas. Data were analyzed using descriptive statistics, correlations, and paired samples t ‐tests. Findings: Paired samples t ‐tests showed a significant improvement ( p < .01) as a result of the educational intervention on all three tests covering the six basic topics. Conclusions: The knowledge of the nurses on topics of basic rehabilitation nursing significantly increased as a result of the educational program. Clinical Relevance: Rehabilitation nurses interested in international travel and developing professional relationships with nurses in China can provide education to promote our specialty practice overseas.